Insulin resistance indices and coronary risk in adults from Maracaibo city, Venezuela: A cross sectional study [version 1; referees: 1 approved with reservations] (2018)
Background: Insulin resistance (IR) is a metabolic disorder related to atherosclerosis. Its measurement is of great importance not only as a marker of diabetes but also for cardiovascular disease. The aim of this research study was to evaluate the relationship between various IR indices and coronary risk in an adult population from Maracaibo city, Venezuela. Methods: The Maracaibo City Metabolic Syndrome Prevalence Study is a descriptive, cross-sectional study with random and multi-stage sampling. In this sub study, 1272 individuals of both genders were selected with the measurement of basal insulin and coronary risk according to the Framingham-Wilson formula calibrated for our population. The insulin resistance indices evaluated were HOMA2-IR, triglycerides and glucose index (TyG) and triglycerides/HDL ratio (TG/HDL). The predictive capacity and association between each index and the coronary risk event in 10 years were determined. Results: Of the evaluated population, 55.2% were female, 34.8% had a coronary risk ≥5% in 10 years, with the TG/HDL and TyG indices showing the highest AUC 0.712 (0.681-0.743) and 0.707 (0.675-0.739), respectively; compared to HOMA2-IR. Both were also the indices most associated with increased coronary risk, especially TG/HDL ≥3 with a higher association [OR = 2.83 (1.74-4.61); p<0.01] after multivariable adjustment. Conclusions: TyG (≥4.5) and TG/HDL (≥3) indices showed a great predictive capacity of higher coronary risk, with being TG/HDL more associated even after adjusting for abdominal obesity and hs-CRP. Therefore, these represent useful tools for determining IR.